1988
DOI: 10.1007/bf01787822
|View full text |Cite
|
Sign up to set email alerts
|

Do weather, day of the week, and address affect the rate of attempted suicide in Hong Kong?

Abstract: Summary. In the whole year of 1986, psychiatrists saw a total of 307 attempted suicide cases presenting to a regional general hospital in Hong Kong, whether admitted or not. They were committed by 295 different people. There was no significant correlation between the number of attempts and the temperature, relative humidity, rainfall or relative duration of sunshine. Comparison with the general population revealed no evidence that suicide attempters were more likely to live in high density public housing block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 27 publications
1
32
1
Order By: Relevance
“…Likewise, a study of weather effects on people should certainly represent multiple locations (hopefully of varying latitude) in order to avoid unknown local variables. Unfortunately, many past studies have made claims about relationships between suicide and weather variables based on a single, relatively small study area (i.e., city or county) and/or a single year of data (Breuer et al 1986;Chiu 1988;Deisenhammer et al 2003;Partonen et al 2004a;Salib 1997;Salib and Gray 1997;Schory et al 2003;Wang et al 1997). None of the articles listed above are published in meteorology or climatology journals.…”
Section: Inconsistent Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…Likewise, a study of weather effects on people should certainly represent multiple locations (hopefully of varying latitude) in order to avoid unknown local variables. Unfortunately, many past studies have made claims about relationships between suicide and weather variables based on a single, relatively small study area (i.e., city or county) and/or a single year of data (Breuer et al 1986;Chiu 1988;Deisenhammer et al 2003;Partonen et al 2004a;Salib 1997;Salib and Gray 1997;Schory et al 2003;Wang et al 1997). None of the articles listed above are published in meteorology or climatology journals.…”
Section: Inconsistent Methodsmentioning
confidence: 95%
“…Some studies, albeit relatively few, have found that there are no associations between meteorological variables and suicide (Chiu 1988;Deisenhammer 2003;Digon and Bock 1966;Dixon and Shulman 1983;Pokorny 1966;Pokorny et al 1963), but even studies that identify positive weather-suicide connections often yield contradictory results. This could be attributed to the fact that some studies analyze multiple (as many as 46) meteorological variables (Deisenhammer 2003).…”
Section: Introductionmentioning
confidence: 91%
“…The absence of seasonality was interpreted as dependent upon the minor relevance of psychiatric and biological factors (i.e. mental disorders and neurohormonal circannual rhythms, respectively) and was taken as proof of the pre-eminence of psychological and social factors in non-fatal self-harming behaviour [8,39]. In his study concerning attempted suicides in Hong Kong, Chiu found no evidence of seasonal variation nor was there any relationship with weather indicators.…”
Section: Discussionmentioning
confidence: 99%
“…Meteorological factors and the seasonal occurrence of mental disorders leading to suicidal ideation are thought to be the main causes for seasonal variation in suicides [3][4][5][6][7]. Attempted suicide also shows a seasonal pattern of occurrence, although this pattern differs from that observed for suicide in several ways [8][9][10]. Non-fatal selfharming behaviour, however, is qualitatively different from suicidal behaviour with a lethal outcome; while the aim of suicide is to bring about one's own death, relational and communicative intentions often prevail in self-harming behaviour [11,12].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation